Animal Health Modeling & Simulation Society: a new society promoting model‐based approaches in veterinary pharmacology. Issue 5 (29th May 2013) - Mochel, J. P.; Gabrielsson, J.; Collard, W.; Fink, M.; Gehring, R.; Laffont, C.; Liu, Y.; Martin‐Jimenez, T.; Pelligand, L.; Steimer, J.‐L.; Toutain, P.‐L.; Whittem, T.; et al.
Abstract : The Animal Health Modeling & Simulation Society (AHM&S) is a newly founded association (2012) that aims to promote the development, application, and dissemination of modeling and simulation techniques in the field of Veterinary Pharmacology and Toxicology. The association is co‐chaired by Pr. Johan Gabrielsson (Europe), Pr. Jim Riviere (USA), and secretary Dr. Jonathan Mochel (Switzerland). This short communication aims at presenting the membership, rationale and objectives of this group.